2023
DOI: 10.1021/jacs.3c02584
|View full text |Cite
|
Sign up to set email alerts
|

An Efficacy and Mechanism Driven Study on the Impact of Hypoxia on Lipid Nanoparticle Mediated mRNA Delivery

Abstract: Hypoxia is a common hallmark of human disease that is characterized by abnormally low oxygen levels in the body. While the effects of hypoxia on many small molecule-based drugs are known, its effects on several classes of next-generation medications including messenger RNA therapies warrant further study. Here, we provide an efficacy- and mechanism-driven study that details how hypoxia impacts the cellular response to mRNA therapies delivered using 4 different chemistries of lipid nanoparticles (LNPs, the fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In brief, our strategy involves co-delivery of adenosine triphosphate (ATP, the cellular currency used to translate mRNA into protein) within mRNA LNPs. 31,32 Specifically, we reveal that our ATP co-delivery strategy results in greater amounts of protein expression across eight different LNP chemistries, three different cell lines, two different oxygenation protocols, and for mRNA encoding for intracellular and secreted proteins. studies are then performed to confirm that our approach is able to increase both intracellular and secreted protein expression levels in mice without impacting the innate biodistribution properties of parent mRNA LNPs (i.e., analogous mRNA LNP formulations without ATP).…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In brief, our strategy involves co-delivery of adenosine triphosphate (ATP, the cellular currency used to translate mRNA into protein) within mRNA LNPs. 31,32 Specifically, we reveal that our ATP co-delivery strategy results in greater amounts of protein expression across eight different LNP chemistries, three different cell lines, two different oxygenation protocols, and for mRNA encoding for intracellular and secreted proteins. studies are then performed to confirm that our approach is able to increase both intracellular and secreted protein expression levels in mice without impacting the innate biodistribution properties of parent mRNA LNPs (i.e., analogous mRNA LNP formulations without ATP).…”
Section: ■ Introductionmentioning
confidence: 93%
“…Here, we present a unified strategy to increase the amount of mRNA-encoded protein expressed by target cells in vitro and in vivo following treatment with mRNA LNPs (Figure ). In brief, our strategy involves co-delivery of adenosine triphosphate (ATP, the cellular currency used to translate mRNA into protein) within mRNA LNPs. , Specifically, we reveal that our ATP co-delivery strategy results in greater amounts of protein expression across eight different LNP chemistries, three different cell lines, two different oxygenation protocols, and for mRNA encoding for intracellular and secreted proteins. Mechanistic studies on intracellular biochemical pathways, cellular association properties, and endosomal escape parameters are then performed to better understand how and why our ATP co-delivery strategy increases the amount of LNP-delivered mRNA into protein.…”
Section: Introductionmentioning
confidence: 96%
“…As such, optimization of the chemistries and molar ratios of each of these components is a large area of research in the field of mRNA delivery. 95,96…”
Section: Orf Modificationsmentioning
confidence: 99%
“…Each of these components is tunable, and modulation of each can cause changes in the size, polydispersity index, charge, encapsulation efficiency, biodistribution, and overall efficacy of the LNPs. As such, optimization of the chemistries and molar ratios of each of these components is a large area of research in the field of mRNA delivery. , …”
Section: Introduction To Mrnamentioning
confidence: 99%
“…In additional examples, adding additional excipients like tannic acid (TA) could also facilitate the endosomal escape of the LNPs in MDCK cells . They also reported that hypoxia decreased the efficacy of LNPs due to differences in ATP in normoxic vs hypoxic cells rather than in how cells respond to mRNA LNPs . A follow up work is to develop a unified strategy by codelivering mRNA and ATP inside LNPs, which may have the potential for treating hypoxic diseases …”
Section: Therapeutic Nucleic Acid Delivery Strategiesmentioning
confidence: 99%